Essential Cognitive Psychology - Parkin Alan J (Psychology Press, Ltd, 2000)
This textbook provides a clear, fundamental grounding in cognitive psychology for beginning undergraduates. Preface, The Origins of Cognitive Psychology, Visual Perception, Attention, Memory: Short-Term Storage, Memory: Long-Term Store, Memory: Codes and Processes and Loops, Memory: Remembering and Forgetting, Knowledge, Imagery, Language: Speech Recognition, Language: World Recognition and Reading, Language: Comprehension, Language: Speaking and Thinking, Reasoning, Problem Solving, Glossary, References, Author and subject Index, Illustration Credits.